Elucidating the expression and role of cGAS in pan-cancer using integrated bioinformatics and experimental approaches - Zhen Lian; Xue Liu; Xue Li (BMC Cancer)
Abstract cGAS plays an important role in regulating both tumor immune responses and DNA damage repair. Nevertheless, there was little research that comprehensively analyzed the correlation between cGAS and the tumor microenvironment, immune cell infiltration, and DNA damage repair in different cancers. In this study, The Cancer Genome Atlas (TCGA) and Cancer Cell Line Encyclopedia (CCLE) data were used to analyze the mRNA expression and genomic alterations of cGAS in pan-cancer. The HPA database was used to explore the protein levels of cGAS in normal tissues and cancers. Correlation analysis were performed to explore the role of cGAS in interferon expression, immune cell infiltrations, DNA damage repair, and predictive immune markers. The prognostic value of cGAS was analyzed using survival data from the TCGA, Kaplan-Meier plotter database, and PrognoScan database. Lastly, the role of cGAS in DNA damage repair signaling and interferon signaling was validated in NSCLC cell lines. The results showed that cGAS was widely expressed in human normal tissues and various cancers, and the expression of cGAS was significantly upregulated in almost all of the solid cancers. Genomic analysis indicated that the expression of cGAS was positively correlated with copy number levels, while negatively correlated with the methylation levels of cGAS promoter. In addition, the level of cGAS was positively correlated with type I interferons expression, infiltration levels of most immune cell types, TMB and MSI levels, stromal and immune scores, and DNA damage repair gene sets including nonhomologous end joining and homologous recombination pathway. Survival analysis indicated that cGAS levels were associated with patient prognosis in several cancers. Lastly, in vitro study showed knockdown of cGAS expression inhibits the DNA damage repair signaling pathway and interferon signaling in NSCLC. In conclusions, cGAS is wildly activated in human cancers, which might participate in regulating cancer immunity and DNA damage repair. cGAS could be used as an effective target for cancer treatment and might be a potential predictive immune marker.